Scheduling of irrigation for wheat (Triticum aestivum) under restricted water supply in Narmada region - MALIWAL, G L; PATEL, J K; KASWALA, R R; PATEL, ML; BHATNAGAR, R; PATEL, J C (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during winter season (rabi) of 1994-95 to 1996 -97 at Khandha, Gujarat to study the effect of irrigation schedule on yield and quality ufwheat (Triticum aestivum L. emend. Fiori & Paol.) under restricted water supply. The treatments conprised 8 levels of irrigation schedule. Results indicated that 4 irrigtations at pre-sowing, crown root initiation, tillering and flowcring under restricted watcr supply gave consistently higher grain yield of wheat during all the years and also in pooled. The water-use efficiency was also higher with this treatment. The quality of wheat grain (lysine and tryptophan) does not affect due to reduction in number of irrigation under constraint of irrigation water than normal recommended irrigation.